2020
DOI: 10.3390/en13195079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hybrid-nano/Paraffin Organic Phase Change Material for Thermal Energy Storage Applications in Solar Thermal Systems

Abstract: In this work, the experimental investigations were piloted to study the influence of hybrid nanoparticles containing SiO2 and CeO2 nanoparticles on thermo-physical characteristics of the paraffin-based phase change material (PCM). Initially, the hybrid nanoparticles were prepared by blending equal mass of SiO2 and CeO2 nanoparticles. The hybrid-nano/paraffin (HnP) samples were prepared by cautiously dispersing 0, 0.5, 1.0, and 2.0 percentage mass of hybrid nanoparticles inside the paraffin, respectively. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…It has been found that adding 1% nanoparticles to paraffin is the perfect amount to improve thermal conductivity. Thus, the thermal storage properties are improved, as shown in Figure 9 [54,55].…”
Section: Aerogelmentioning
confidence: 98%
“…It has been found that adding 1% nanoparticles to paraffin is the perfect amount to improve thermal conductivity. Thus, the thermal storage properties are improved, as shown in Figure 9 [54,55].…”
Section: Aerogelmentioning
confidence: 98%
“…Due to the fact that nanoscale fills are typically defectfree, the applications in the field of polymeric composite region setting have the potential to circumvent the limitations of the conventional micrometre scale. Consistent and ubiquitous inclusion of nanoparticles creates a wide interfacial contact surface, which affects relaxation behaviour as well as physical, molecular mobility, and thermal performance (Pasupathi et al 2020). Jiang et al (2013) studied the effect of nano-silica on the properties of polymer matrix composites containing urea formaldehyde.…”
Section: Influence Of Interface Between Nanoparticles and Natural Fib...mentioning
confidence: 99%
“…The controller is responsible for transferring batteries to the motor. The pedal is linked to a potentiometer, which transmits a signal to control indicating how much power to apply [26,27,28]. When the vehicle comes to a complete stop, the controller can provide low gain, maximum capacity when the pedal is completely pushed, or anywhere in between.…”
Section: Ev Conversion Processmentioning
confidence: 99%